Review On Improving Patient Compliance With Extended Release Matrix Tablets - Turke, Vanashri; Prasad Rai, Janki (Journal of Neonatal Surgery, 2025)
The study explores the necessity, advantages, and techniques of extended-release matrix tablets for continuous drug delivery at predictable rates and reproducible kinetics. It discusses different formulation methods, including wet granulation, direct compression, or solid particle dispersion within a porous matrix made of polymers like HPMC, guar gum, xanthan gum, pectin, and chitosan. The matrix controls drug release rate, with release retardants like HPMC aiding in extended release. Various matrices, such as hydrophilic, hydrophobic, mineral, or biodegradable types, can be used. Some drugs formulated as extended-release matrix tablets include Ambroxol HCl, Clarithromycin, and Indomethacin. These tablets can improve patient compliance by reducing total dose and dosage regimen, which can help treat chronic diseases. The review highlights the types of matrices, mechanisms involved, and evaluation studies.